Resonance characterization of microring resonator for optical biosensor - Mohd Salleh, Mohd Hazimin (2013)
Currently, biosensing devices operate in the communication wavelength band between λ = 1300 – 1550 nm using the silicon (Si) based material upon which they are based. However silicon is not transparent to the visible wavelength region. In order to overcome this problem, we proposed a polymer material that could utilize the visible region, that is usually perform in biological based detection. The use of polymeric materials for micro and nano structures recently has gained major interest of multi disciplinary research since it allows rapid and straightforward fabrication process. In this paper, we show the potential use of polymer micro resonator structures for optical biosensing applications using COMSOL Multiphysics as modelling software. The detection principle is based on the phenomenon that, when the refractive index surrounding the micro resonator changes, there is a shift of resonance wavelength that can be monitored inline with biological interaction. In the simulated result presented here, the light source is launched into the input waveguide and the output resonance is characterized by the output port waveguide. Various ring radii (30, 40 and 50 μm) and surrounding refractive index have been successfully simulated. The resonance patterns from the output waveguide, which extend within visible wavelength (400 - 800 nm) and communication wavelength region (1300 – 1550 nm) were obtained. Modelling calculation and simulated results of the spectral response are presented. Comparing with communication wavelength region, we found that the resonances peak characteristics are sufficiently within the visible wavelength region and it is suitable to be utilized in both labeled and label-free optical biosensor scheme. The reasons for discrepancies from the simple model calculations are discussed, particularly on why the depth of resonance is not as deep as predicted by theory. However, the simulated resonances outputs are sufficiently well defined to be used in optical biosensing application.